Testosterone replacement maintains smooth muscle content in the corpus cavernosum of orchiectomized rats - Graziele Halmenschlager; Ernani Luis Rhoden; Gabriela Almeida Motta; Lucas Sagrillo Fagundes; Jorge Luiz Medeiros, Jr.; Rosalva Meurer; Cláudia Ramos Rhoden (Asian Journal of Urology)
Objective: To evaluate the effects of testosterone (T) on the maintenance of corpus cavernosum (CC) structure and apoptosis. Methods: Animals were divided into three groups: sham operation group (n = 8) underwent sham operation; Orchiectomized (Orchiec)+ oily vehicle group (n = 8) underwent bilateral orchiectomy and received a single dose of oily vehicle by intramuscular injection (i.m.) 30 days after orchiectomy; and Orchiec + T group (n = 8) underwent bilateral orchiectomy and received a single dose of T undecanoate 100 mg/kg i.m. 30 days after the surgery. Animals were euthanized 60 days after the beginning of the experiment with an anesthetic overdose of ketamine and xylazine. Blood samples and penile tissue were collected on euthanasia. Azan's trichrome staining was used to evaluate smooth muscle, Weigert's Fucsin-Resorcin staining was used to evaluate elastic fibers and Picrosirius red staining was used to evaluate collagen. Apoptosis was evaluated using TUNEL technique. Results: T levels decreased in Orchiec + oily vehicle when compared to sham operation and Orchiec + T groups (p < 0.001). T deprivation reduced trabecular smooth muscle content and penile diameter and T replacement maintained both parameters (p = 0.005 and p = 0.001, respectively). No difference was observed in the content of sinusoidal space (p = 0.207), elastic fibers (p = 0.849), collagen (p = 0.216) and in apoptosis (p = 0.095). Conclusion: Normal testosterone levels maintain CC smooth muscle content and do not influence elastic fibers, collagen content and apoptotic index. Further studies should be performed in order to investigate the mechanisms by which androgen mediates its effects on CC structure.